PERAN PENDAMPING LEMBAGA BATHIN LIMO BOMBAN MINEH DALAM MEMBERDAYAKAN MASYARAKAT SUKU SAKAI KABUPATEN SIAK - Rosmita; Listiawati; Fatmawati; Ade Novia Septrianti (JURNAL SOSIO-KOMUNIKA, 2023)
The purpose of this study is to find out the role of assistance carried out by the Bathin Limo Bomban Mineh Institute in empowering the people of West Minas. As for this type of research is descriptive qualitative, with research informants totaling 6 (six) people with categories namely 1(one) person as key informant and 5 (five) supporting informants. The results of this study are that there is a companion role carried out by the bathin limo bomban mineh institution such as providing educational scholarship assistance for Sakai tribal children who are assisted by companies operating in the area and discussion by inviting the Sakai tribe community to be able to make changes towards better, providing direction and training in making handicrafts.